Formal Techniques for Distributed Systems Joint 14th IFIP WG 6.1 International Conference, FMOODS 2012 and 32nd IFIP WG 6.1 International Conference, FORTE 2012, Stockholm, Sweden, June 13-16, 2012. Proceedings - Giese, Holger; Rosu, Grigore; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 14th IFIP WG 6.1 International Conference on Formal Methods for Open Object-Based Distributed Systems, FMOODS 2012, and the 32nd IFIP WG 6.1 International Conference on Formal Techniques for Networked and Distributed Systems, FORTE 2012, held in Stockholm, Sweden, in June 2012, as one of the DisCoTec 2012 events. The 16 revised full papers presented were carefully reviewed and selected from 42 submissions. They cover a wide range of topics combining theory and practice in application areas of telecommunication services, Internet, embedded and real-time systems, networking and communication security and reliability, sensor networks, service-oriented architecture, and Web services.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Computer Science; Computer Communication Networks; Programming Techniques; Software Engineering; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs; Mathematical Logic and Formal Languages